A Comprehensive Review of the Diagnosis and Treatment of Polycystic Ovary Syndrome - Ribeiro, Victoria (2024)
This article aims to conduct a comprehensive and critical review of contemporary approaches to the diagnosis and treatment of polycystic ovary syndrome, using the PubMed database with the terms "Polycystic Ovary Syndrome", "Diagnosis" and "Treatment". The results demonstrate that advances in the diagnosis of polycystic ovary syndrome (PCOS) have been significant, especially with the integration of new technologies and more precise guidelines. Innovations in ultrasound, such as counting antral follicles and assessing the thickness of the lining of the uterus, have improved diagnostic accuracy, while anti-Müllerian hormone (AMH) has proven to be a valuable marker in identifying PCOS. These advances are critical to early detection and appropriate management of the condition, providing a solid foundation for effective treatment. When it comes to treatment, the multimodal approach remains the most effective, with lifestyle modifications and pharmacological therapies playing crucial roles in managing the symptoms and comorbidities associated with PCOS. The combination of interventions, such as hormonal contraceptives, antiandrogenic agents, and insulin resistance medication, must be carefully tailored to each patient to optimize clinical outcomes. However, it is clear that personalization of treatment and the need for more research into the long-term efficacy and safety of treatments are essential to improving the therapeutic approach and ensuring effective management of PCOS.